PERAN MANAJERIAL KEPALA BIDANG DI LINGKUNGAN BADAN PERENCANAAN, PENELITIAN DAN PENGEMBANGAN DAERAH (BAPPEDA) KOTA BENGKULU - Meiko, Wanhuri; Yogopriyatno, Jatmiko; Hardayani, Yorry (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
The performance of employees within BAPPEDA Bengkulu City was found to have a number of employees who have not been able to carry out their duties properly because their understanding of their main duties and functions is still low, and there is still domination from superiors to subordinates. Therefore, this study aims to describe and describe the managerial role of the head of the field within BAPPEDA Bengkulu City, by adopting the theory of managerial roles proposed by Mitzberg (1990) which divides these roles into three roles namely; interpersonal, informational, and decisional. The approach used in this research is descriptive qualitative, with data collection through observation, interviews, and documentation. Analysis of the data collected was carried out simultaneously through data reduction, data presentation, and conclusion drawing and verification. The results showed that the managerial role of the head of the field at BAPPEDA Bengkulu City has not been optimized due to the constrained implementation of the minformasiomnal role and the decision-making role of the head of the field. This happens because the dissemination of information often does not reach all employees because it is not conveyed in a way that is easily understood and relevant, and there is still dominance by the head of the field in decision making. To optimize the managerial role in decision-making needs to be balanced with increasing subordinate participation and adopting a more collaborative and inclusive approach to optimize the managerial role and improve overall organizational performance